OTOMATISASI SELEKSI CALON PENERIMA BEASISWA MENGGUNAKAN ALAT BANTU SISTEM PENUNJANG KEPUTUSAN DENGAN METODEWEIGHTED PRODUCT (WP) - Vratiwi, Septiana; Wiwita, Risma; Syafti, Okviani; Efendi, Efendi; Sefrinal, Sefrinal (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2022)
Scholarships are a work program that exists in every college and school. The scholarship program is held to ease the burden on students in taking their studies. STKIP Pesisir Selatan is one example of a university that has many scholarship programs to be distributed to every student and student who is financially underprivileged but has the determination to continue their education and excel during their schooling. The purpose of this research is to process the automatic selection of scholarship recipients using a system through a decision support system combined with the Weigted Product method so that prospective scholarship recipients can be directly determined and will make it easier for universities to determine which prospective students will be selected. Of the 5 samples used, the 3 highest scores obtained with percentages of 0.27 (Meri Anjeli), 0.27 (Ririn Dwi Putri), 0.23 (Fauzia Ramanda) which will be used as guidelines in making decisions on the selection of scholarship recipients.